Country music : live at the Ryman : a concert celebrating the film by Ken Burns [videorecording (DVD)] - Duncan, Dayton; Bentley, Dierks; Cash, Rosanne; Crowell, Rodney; Gatlin, Larry; Giddens, Rhiannon, 1977-; Gill, Vince; Mattea, Kathy; Secor, Ketcham; Skaggs, Ricky; Williams, Holly, 1981-; Yoakam, Dwight; et al. (2019)
Filmmaker Ken Burns invited some of country music's finest artists to gather at Ryman Auditorium to celebrate the launch of his PBS series Country Music. Burns curated an evening of selected highlights from the series combined with performances of the music's iconic songs by some of country's finest artists including Dierks Bentley, Rosanne Cash, Vince Gill, Kathy Mattea, Marty Stuart, and more. The evening is a musical journey tracing the evolution of country music and its many branches while highlighting its foundational stars with songs performed from: Jimmie Rodgers, The Carter Family, Hank Williams, Bob Wills, Loretta Lynn, Johnny Cash, Bill Monroe, Patsy Cline, Dolly Parton, Merle Haggard, Kris Kristofferson, and many more.